The Effect of Achievement Motivation, Self-Efficacy, and Social Support on Students’ Academic Flow at Cipta Wacana Christian University in Post-Covid-19 Pandemic Era - Abd. Syakur; Suhadianto Suhadianto (At- Ta'lim : Jurnal Pendidikan, 2025)
The current study focuses on exploring students’ learning process and task management to obtain comprehensive learning outcomes. Not all students are able to focus and enjoy the learning process in Post-COVID-19 era, situating the changes on education system, interactions between students, and etc. Based on the preliminary research, 90% of Cipta Wacana Christian University students experienced feelings of boredom, stagnation, and stress during the online learning process. The current study aims to determine the influence of motivation, self-efficacy, and social relationships on academic achievement, recruiting 80 respondents as the sample of the study ranging to semesters 1 to 8. A quantitative study, piloting multiple correlation analysis techniques with the Spearman method were administered to explore the relationship between the various variables and gain a deeper understanding on how achievement motivation, self-efficacy and social support, affecting the students’ academic flow level. Furthermore, the study uncovered that self-efficacy and social support significantly contributed to academic flow. However, the achievement motivation variables (X1) and self-efficacy (X2) did not have any significant impact on academic flow (Y). Only the social support variable (X3) showed a significant influence, reflecting a novice and distinctive finding with the previous studies. The Beta coefficient for the achievement motivation variable contributed 22.2% to academic flow. It is lower than the Beta coefficient value for the self-efficacy variable (40.3%) and social support (72.3%). In a nutshell, the three independent variables had a positive direction on increasing achievement motivation, self-efficacy, and social support, contributing to increase the students’ academic flow.